VARIASI SURVIVAL DAN PERTUMBUHAN SUREN (Toona sinensis Roem) ASAL PULAU SUMATERA DI UJI PROVENANS PADA UMUR 4 DAN 5 TAHUN - Liliek Haryjanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
A provenance trial of suren (Toona sinensis Roem) is aimed to obeserve the best provenance in adaptation and growth traits. This provenance is used as seed sources for forest rehabilitation in the area of development. Eleven provenances of suren from Sumatera Island was established in Candiroto, Temanggung, Central Java. The plot was designed in a Randomized Completely Block Design (RCBD) comprised of three replicates, 11 provenances and 9 trees per plot with spacing of 3m x 3m. This study showed that tree height, diameter and volume were significant different among provenances at 4 and 5 years age, while significant for survival at 5 years age. Tree height, diameter and volume showed significant and positive correlation with each other. Broad sense heritability value were found fairly good for all traits. Pasaman (West Sumatera) provenance is recommended to be the best seed sourced for plantation under similar site conditions and also genetic improvement programme.